Caesar's Coin dan Hubungan Gereja-Negara dalam Orde Baru - Intan, Benyamin (Verbum Christi: Jurnal Teologi Reformed Injili, 2021)
Even though Indonesia has entered the Post-Soeharto Era for almost a quarter of a century, authoritarianism still needs to be watched out for. The style and behavior of authoritarianism in any part of the world is common to shed blood rather than build peace. This study aims to reveal Jesus' rejection of authoritarianism in government. Since Indonesia's independence, authoritarianism has occurred during the New Order. For 32 years, this government suppressed the development of democracy which also had an impact on the economic, education, health and religious fields. In this study, the authors found that excessive vigilance and fear of the presence of a Zealot-style theocracy model of government through the issue of the Islamic state and Islamic society has led to absolute loyalty and partiality without reserve from the Church towards the Government. The author argues that the church, as a spiritual institution, has been “politicized”, besides the church has lost its critical and corrective functions.